Perbaikan Kualitas Telur Ayam Ras Melalui Perubahan Waktu Pemberian Dan Kandungan Protein Ransum - Y. Heryandi (Universitas Andalas, 2006)
The experiment was carried out to study the effect of feeding time and protein content of diets on the egg weigh, the quality of egg shell and haugh unit. One hundred and sixty two laying hens of about 20-34 weeks of age were divided into 3 groups and fed diets in 3 different levels of protein of 12, 15 and 18 %.The diets were offered for 28 days in 3 different times of 08.00, 18.00 and 04.00 everyday. Parameters measured included: number of egg production, egg weigh, dick and weight of egg shell, HU and ratio of yolk and albumin. The data were statistically analyzed for variance analysis in completely randomized factorial design of 3 x 3. The ambient temperature during the experiment ranged from 26,7oC to 29,6oC, while the humidity of 65 to 92 %. The egg shell qualities were significantly improved by changing of the feeding time. The level of protein diet gave significant effect on the egg weigh, egg shell quality and ratio of egg yolk and albumin.